Indonesian K-Pop fans: The relationship between ARMY-BTS identity and their demographic - Yayah Cheriyah; Amanda Rochima Hadi (Universitas Negeri Yogyakarta, 2022)
This article analysed the fans’ identity among K-Pop fans in Indonesia, especially BTS fans. The study aimed to explore how these fans express their identity as fans both internally and externally despite negative stereotyping of loyal K-Pop fans. Using a quantitative method through online surveys based on the fans-identity scale approach, the research surveyed a total of 243 BTS fans in Indonesia. Results showed that BTS fans had a positive tendency toward overall fan characteristics. None of the characteristics showed a negative score. It indicated that there was a high loyalty among the fans. Almost all six-behaviour dimensions observed correlated with all seven fans-identity characters. “Specific social media accounts followed” showed no correlation with “enjoyment” and “identity” respectively. However, high loyalty and a large number of fan-based did not translate into monetization for official merchandise. Results showed a low number of purchases for official merchandise and global membership package.